2017
DOI: 10.5604/12321966.1234004
|View full text |Cite
|
Sign up to set email alerts
|

Serological evidence of exposure to zoonotic tick-borne bacteria in pheasants (Phasianus colchicus)

Abstract: Introduction and objective. Previous studies on tick-borne pathogens in the avian population have focused mainly on the detection of the agents in ticks collected from birds, but data about the presence of tick-borne bacteria in these animals are scant. The aim of the presented study was to verify the exposure to some zoonotic tick-borne bacteria, in particular, Anaplasma phagocytophilum, Borrelia burgdorferi sensu lato, Coxiella burnetii, and the Rickettsia species of the Spotted Fever Group (SFG), in pheasan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The detected prevalence could include antibodies against R. conorii, as well as other SFG rickettsiae due to the common antigens [7]. In fact, several SFG rickettsiae, mainly R. conorii, R. helvetica, R. massiliae, R. slovaca, R. aeschlimannii, R. africae, R. monacensis, R. roultii were circulating in Italy at the sampling time, as observed in molecular investigations in animals and ticks [17].…”
Section: Rickettsia Spp In Birds and Their Ticksmentioning
confidence: 77%
See 2 more Smart Citations
“…The detected prevalence could include antibodies against R. conorii, as well as other SFG rickettsiae due to the common antigens [7]. In fact, several SFG rickettsiae, mainly R. conorii, R. helvetica, R. massiliae, R. slovaca, R. aeschlimannii, R. africae, R. monacensis, R. roultii were circulating in Italy at the sampling time, as observed in molecular investigations in animals and ticks [17].…”
Section: Rickettsia Spp In Birds and Their Ticksmentioning
confidence: 77%
“…A serological survey was carried out in pheasants (P. colchicus) to verify the occurrence of antibodies against some tick-borne pathogens. All the tested pheasants lived in an area of central Italy with conditions favorable for ticks' diffusion, such as a rich vegetation and various large and small mammals [17]. The 17.75% of the examined animals were positive to R. conorii antigen [17].…”
Section: Rickettsia Spp In Birds and Their Ticksmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the animals mentioned above, wild brown hares captured in central Italy were found to carry anti- Borreliella antibodies [ 258 ], and one blood sample from a wild boar was positive for Borreliella DNA [ 259 ]. Additionally, farm-reared pheasants were seropositive [ 260 ] and feral pigeons were positive for the presence of Borreliella DNA [ 261 ]. Finally, it was demonstrated that Borreliella DNA was found in blood samples collected from the heart of hunted red deer [ 262 ], as well as antibodies against Borreliella in blood samples from fallow deer from farms [ 263 ].…”
Section: Lyme Diseasementioning
confidence: 99%